2014
DOI: 10.1016/j.chemosphere.2014.03.079
|View full text |Cite
|
Sign up to set email alerts
|

Fungal enzyme production and biodegradation of polychlorinated dibenzo-p-dioxins and dibenzofurans in contaminated sawmill soil

Abstract: Soils that are contaminated with the most recalcitrant organic contaminants, such as high molecular weight polyaromatic hydrocarbons (HMW PAH) and polychlorinated dibenzo-pdioxins and dibenzofurans (PCDD/F), cannot be degraded efficiently by conventional composting. The only available treatment method for these soils, which destroys the contaminants, is combustion at high temperature. This thesis examines three alternative fungal methods to treat these soils: 1) treatment with fungal enzymes, 2) treatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(15 citation statements)
references
References 116 publications
0
15
0
Order By: Relevance
“…This suggested that growth on poplar wood significantly altered T. versicolor's expression of enzymes that hydrolyze methyl and benzoic acid groups. Catechol and benzoate were important products in lignin degradation (Aranda et al 2010;Sari et al2012;Cruz-Morató et al 2013;Anasonye et al 2014), but were also produced during aminobenzoate degradation. From these results it was inferred that lignin degradation may have been related to aminobenzoate degradation or have similar intermediate compounds.…”
Section: Validation Of the Gene Expression Profiles By Qrt-pcrmentioning
confidence: 99%
“…This suggested that growth on poplar wood significantly altered T. versicolor's expression of enzymes that hydrolyze methyl and benzoic acid groups. Catechol and benzoate were important products in lignin degradation (Aranda et al 2010;Sari et al2012;Cruz-Morató et al 2013;Anasonye et al 2014), but were also produced during aminobenzoate degradation. From these results it was inferred that lignin degradation may have been related to aminobenzoate degradation or have similar intermediate compounds.…”
Section: Validation Of the Gene Expression Profiles By Qrt-pcrmentioning
confidence: 99%
“…Extracellular enzymes of white-rot fungi (WRF) are characterized by their capacity to degrade the complex structure of lignin, which also enables them to degrade a wide range of resistant pollutants including synthetic dyes, chlorophenols, polychlorinated biphenyls and polycyclic aromatic hydrocarbons [18,19,20,21,22,23]. WRF and their lignin modifying enzymes (LMEs) have been investigated recently for the degradation of a broad spectrum of PPCPs [24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Such pollutants, namely polychlorinated dibenzo- p -dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs), are considered the most toxic group of Persistent Organic Pollutants (POPs) (WHO, 2016). Due to their physicochemical properties, dioxins can persist in the environment and bioaccumulate in the organisms of a given ecosystem, including bacteria, fungi, plants, animals, and humans (Field and Sierra-Alvarez, 2008; Ishida et al, 2010; Anasonye et al, 2014; Hanano et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%